Insomnia in the hospitalized elderly: factors related to nursing care - Lauriana Medeiros Costa; Raimunda Medeiros Germano (Rev Rene)
This exploratory-descriptive study of qualitative approach broaches the issue of insomnia in the hospitalized elderly. It aims at identifying factors related to insomnia at the hospital, learning about nursing actions concerning the assessment of the patient, treatment and prevention of insomnia. Nurses, technicians and nursing assistants were interviewed in a public hospital in Natal-RN. It was observed that insomnia has multiple causes like: difficulty to adapt to the routine and environment of the hospital, disease, anxiety, idleness and physical and psychological discomfort. Some therapeutic and preventive actions were suggested like the promotion of comfort, reduction of anxiety, psychological orientation and support, and administration of drugs when prescribed.